Nocturnal blood pressure decline based on different time intervals and long-term cardiovascular risk: the Ohasama Study - Michihiro Satoh; Kei Asayama; Masahiro Kikuya; Ryusuke Inoue; Megumi Tsubota-Utsugi; Taku Obara; Keiko Murakami; Ayako Matsuda; Takahisa Murakami; Kyoko Nomura; Hirohito Metoki; Yutaka Imai; et al. (Clinical and Experimental Hypertension, 2018)
A diminished nocturnal decline in blood pressure (BP) represents a risk factor for cardiovascular disease. To define daytime and nighttime ambulatory BP, clock time-dependent methods are used when information on diary-based sleeping time is unavailable. We aimed to compare fixed-clock intervals with diary records to identify nocturnal BP declines as a predictor of long-term cardiovascular risk among the general population. Data were obtained from 1714 participants with no history of cardiovascular disease in Ohasama, Japan (mean age, 60.6 years; 64.9% women). We defined extreme dippers, dippers, non-dippers, and risers as nocturnal systolic BP decline ≥20%, 10–19%. 0–9%, and <0%, respectively. Over a mean follow-up period of 17.0 years, 206 cardiovascular deaths occurred. Based on diary records, multivariable-adjusted hazard ratios (HRs) for cardiovascular death compared with dippers were 1.24 (95% confidence interval [CI], 0.82–1.87) in extreme dippers, 1.21 (0.87–1.69) in non-dippers, and the highest HR of 2.31 (1.47–3.62) was observed in risers. Using a standard fixed-clock interval (daytime 09:00–21:00; nighttime 01:00–06:00), a nighttime 2 h-early shifted fixed-clock (daytime 09:00–21:00; nighttime 23:00–04:00), or a nighttime 2 h-late shifted fixed-clock (daytime 09:00–21:00; nighttime 03:00–08:00), the HR (95%CI) in risers compared with dippers was 1.57 (1.08–2.27), 2.02 (1.33–3.05), or 1.29 (0.86–1.92), respectively. Although use of diary records remains preferable, the standard and nighttime 2 h-early shifted fixed-clock intervals appear feasible for population-based studies.